Prodigiosin hydrogel to promote healing of trauma-infected multidrug-resistant Staphylococcus aureus mice wounds - Xin Wang; Guangfan Meng; Zongyu Zhang; Jiacheng Zhao; Shaoyu Wang; Dongliang Hua; JingZhang; Jie Zhang (International Journal of Pharmaceutics: X)
Wound infections caused by Multidrug-resistant Staphylococcus aureus (MRSA) have been regarded as a challenging problem in clinic for the long time. In this study, based on the excellent antimicrobial effect of prodigiosin(PG) and the ability of hydrogel dressing in terms of tissue repair and regeneration, we prepared the PG hydrogel as a treatment for the wound infection induced by MRSA. Rheological tests indicated that PG hydrogel as a semi-solid gel had good mechanical properties. In ex vitro drug permeation studies and dermatokinetic studies showed that PG hydrogel had high PG permeability and were capable of short-term retention in the skin. In addition, in vivo experiments for mouse skin wounds showed that the serum levels of inflammatory factors including IL-β and other inflammatory factors were reduced, the inflammatory infiltration of tissues was reduced, the transcript levels of genes such as COL1A1 were up-regulated at different stages of wound healing, and the relative abundance of genera such as Desulfovibrio was lowered after treatment with PG hydrogel, which facilitated wound healing in mice. Our study would provide a new solution to the clinical shortage of drugs for the treatment of MRSA infection and provide a research basis for improving the comprehensive values of PG.